Media and Development: The Dysfunctional Alliance - Nelson, Mark (Global Media Journal - German Edition, 2015)
This essay looks at the dysfunctional relationship between overall international development assistance and more specific support to the media sector. While the international donor community sees the potential of independent media in developing countries to contribute to societies’ economic and social progress, international development policies rarely have a coherent, integrated approach to the media sector, and foreign assistance often fails to achieve its goal of helping countries create a sustainable, independent media that acts in the interests of society as a whole. Indeed, leaders of many countries have decided that media—and especially unfettered, independent media—is more likely to be an obstacle, at least to their political fortunes, than a support. The author proposes three ways that the international community could improve its work on media development and build stronger political commitment for independent media. First is strengthening country leadership and ownership of media development initiatives. This requires building local knowledge about the role of media in open societies and about how to manage a strong, independent media system. Second is integration of media development work within the broader development agenda, leveraging more of the 135 billion that donors spend annually on official development assistance. Third is improving data, diagnostics, and learning on the media sector, particularly in developing countries, and creating a better understanding of how country-level media sectors are evolving, and how they can be best supported.